Collectivity in small systems measured with PHENIX at RHIC - Lara, Carlos E. Perez (AIP conference proceedings, 2020)
The study of anisotropic flow provides strong constrains to the evolution of the medium produced in heavy ion collisions and its event-by-event geometry fluctuations. The strength and predominance of these observables have long been related to collective behaviour in the formed medium. Recent results in small systems both at the Relativistic Heavy Ion Collider RHIC and the Large Hadron Collider LHC provide strong arguments for the formation of such medium at those scales. PHENIX has measured the v2 and v3 anisotropic flow coefficients for p+Au, d+Au, and 3He+Au collisions at 200 GeV as well as d+Au at various lower energies. We find that the flow coefficients match the ordering from the initial geometry. Moreover we show that the flow coefficients in all systems are very well described by the predictions from hydrodynamic models [1].